Factors Influencing Farmers' Decision to Participate in the RHL (Forest and Land Rehabilitation) Program in Lengkiti District, OKU Regency - Oktavia, Dina; Munajat; Sari, Fifian Permata; Manggi, Anggi Fatmayati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This research aims to determine what factors influence farmers' decisions to participate in Forest and Land Rehabilitation activities in Lengkiti District, OKU Regency. This study employed a survey approach of research. In this work, logistic regression analysis was utilized to analyze the data. The findings revealed that the independent variables: number of family members, land area, and workdays, significantly affected coffee growers' decisions to participate in the Forest and Land Rehabilitation (RHL) program.